Volume 1: Offshore Technology; Ocean Space Utilization 2003
DOI: 10.1115/omae2003-37151
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mooring System and Sheared Currents on Vortex Induced Motions of Truss Spars

Abstract: Since 1996 Spars have been used as production platform in the Gulf of Mexico. Spar Vortex Induced Motions (VIM) in strong currents like the hurricane and loop currents are an important consideration for the design of the mooring system and risers. This is important for the extreme offsets as well as fatigue in risers and the mooring system. This paper compares the VIM behavior of a truss Spar in sheared currents, like the Hurricane current in the Gulf of Mexico, with tow test results. Experiments have been car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This influence is directly related to the position of the appendages, fairleads and chains on the hull. van Dijk et al (2003) and Irani and Finn (2004) reported that waves have also effect on VIM of a spar. In the same sense, Finnigan et al (2005) presented the first results regarding truss spar VIM in the simultaneous presence of waves and current, which showed that waves in-line with the current direction generally reduce VIM response.…”
Section: Introductionmentioning
confidence: 99%
“…This influence is directly related to the position of the appendages, fairleads and chains on the hull. van Dijk et al (2003) and Irani and Finn (2004) reported that waves have also effect on VIM of a spar. In the same sense, Finnigan et al (2005) presented the first results regarding truss spar VIM in the simultaneous presence of waves and current, which showed that waves in-line with the current direction generally reduce VIM response.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical and experimental studies have been carried out widely on VIMs of cylinders and monocolumn platforms [1,2]. Gonçalves et al investigated the vortex-induced vibration of circular cylinders with very low aspect ratio and small mass ratio [3].…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of predicting full-scale VIMs through model testing was verified. Van Dijk et al 21 further conducted a model test comparing the VIM responses under various simulation methods of incoming current. One method was implemented by dragging the model in calm water, and the other was implemented by generating a current in the basin, respectively.…”
Section: Introductionmentioning
confidence: 99%